“Ce qui ronge”: Poetic Experience and Phenomenological Overtures in Two Collections by Jorge Eduardo Eielson and Blanca Varela - Guardia Hernández, Andrea Milena; Aguiar Mejía, Nasli (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The subjective experience of the Late Modernity seems determined by the loss of its significance, its cognitive reach and of its possibilities to be expressed in an aesthetic way. Two Peruvian collections serve as corpus to reflect on how poetic language faces this circumstance at the beginning of the 21st century. To achieve this objective, the phenomenological claims of Merleau-Ponty serve to center the attention on how, after having explored the limits of their language, the poets materialize a poetic experience that can be read as that of a subject-body that makes language an essential part of its lived experience. This analysis highlights the contribution of phenomenology to literary criticism and enriches the reading of the late works of Eielson and Varela in the framework of contemporary poetry.